Pelaksanaan pembelajaran tematik pada pembelajaran jarak jauh di kelas V - Fauzi, Irfan Sholeh; Rukayah, Rukayah; Budiharto, Tri; Nuswantari, F S (JPI (Jurnal Pendidikan Indonesia): Jurnal Ilmiah Pendidikan, 2021)
This reseach aims to: (1) describe Thematic Learning in Distance Learning (e-learning) (2) describe the school's efforts to optimize Thematic Learning in Distance Learning (e-learning). This research uses a qualitative approach with a case study method. The research subjects involved were the principal, teachers, students, and parents of grade V SD N Tegalayu No. 96 Surakarta. Research data collection techniques using observation and interviews. The validity of the research data used triangulation techniques. Data were analyzed using an interactive model, consisting of data reduction, data presentation, and drawing conclusions. As a result, Thematic Learning in Distance Learning goes according to schedule. Five days a week. The implementation of learning includes the planning stage, the implementation stage, and the evaluation stage. The conclusions of the researchers are: (1) the implementation of thematic learning in distance learning at SD N Tegalayu No.96 Surakarta has run according to the schedule and (2) Efforts in implementing Thematic Learning in Distance Learning involve the efforts of the principal, teachers, students, and parents of students in improving learning optimization.Keywords: thematic learning, e-learning, distance education